Commissioning of the read-out driver (ROD) card for the ATLAS IBL detector and upgrade studies for the pixel Layers 1 and 2 - Balbi, Gabriele; Kugel, Andreas (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2014)
The higher luminosity that is expected for the LHC after future upgrades will require better performance by the data acquisition system, especially in terms of throughput. In particular, during the ﬁrst shutdown of the LHC collider in 2013/14, the ATLAS Pixel Detector will be equipped with a fourth layer - the Insertable B-Layer or IBL - located at a radius smaller than the present three layers. Consequently, a new front end ASIC (FE-I4) was designed as well as a new off-detector chain. The latter is composed mainly of two 9U-VME cards called the Back-Of-Crate (BOC) and Read-Out Driver (ROD). The ROD is used for data and event formatting and for conﬁguration and control of the overall read-out electronics. After some prototyping samples were completed, a pre-production batch of 5 ROD cards was delivered with the ﬁnal layout. Actual production of another 15 ROD cards is ongoing in Fall 2013, and commissioning is scheduled in 2014. Altogether 14 cards are necessary for the 14 staves of the IBL detector, one additional card is required by the Diamond Beam Monitor (DBM), and additional spare ROD cards will be produced for a total of 20 boards. This paper describes some integration tests that were performed and our plan to test the production of the ROD cards. Slices of the IBL read-out chain have been instrumented, and ROD performance is veriﬁed on a test bench mimicking a small-sized ﬁnal setup. This contribution will report also one view on the possible adoption of the IBL ROD for ATLAS Pixel Detector Layer 2 (ﬁrstly) and, possibly, in the future, for Layer 1.
Gesehen am 15.09.2020